2018
DOI: 10.3382/ps/pey049
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drying method temperature, collection method, and marker type on apparent ileal amino acid digestibility in 21-day-old broilers fed corn-soybean meal-barley based diet

Abstract: For accurate estimation of nutrient digestibility, an ideal drying and sampling method is required to preserve the quality of the digesta. A standard corn-soybean meal (corn-SBM) broiler starter diet was fed from d 0 to 10 before birds were placed on the experimental diets until d 21. One hundred and sixty-eight male Cobb 500 broiler chicks were used to evaluate the effect of two drying methods (freeze-dryer vs. forced air-oven) and two drying temperatures (40 vs. 55°C) (Exp 1), while ninety-six chicks were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Therefore, the effect of treatment on the AID of amino acids can still be described as reported because the magnitude of the response to phytase would be the same, regardless of the drying conditions. In addition, the AID coefficients for amino acids in the current trial are similar to the AID of amino acids reported by Cowieson et al (2006) and Olojede et al (2018) using similar drying conditions or greater than those reported by Ravindran et al (2001), also using digesta samples dried at 80 °C. The absolute amino acid digestibility coefficients obtained from any experiment are an estimate of the average amino acid digestibility over the duration of the trial and reported as a point in time measurement.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the effect of treatment on the AID of amino acids can still be described as reported because the magnitude of the response to phytase would be the same, regardless of the drying conditions. In addition, the AID coefficients for amino acids in the current trial are similar to the AID of amino acids reported by Cowieson et al (2006) and Olojede et al (2018) using similar drying conditions or greater than those reported by Ravindran et al (2001), also using digesta samples dried at 80 °C. The absolute amino acid digestibility coefficients obtained from any experiment are an estimate of the average amino acid digestibility over the duration of the trial and reported as a point in time measurement.…”
Section: Discussionsupporting
confidence: 86%
“…The drying methods did not consistently affect the amino acids, but the highest concentrations were observed when the samples were dried at 60°C for most amino acids. In another study, prececal amino acid digestibility did not differ when the digesta samples were freeze‐dried or dried in a forced‐air drying chamber at 40 and 55°C (Olojede et al 2018). We are not aware of any published study describing the effects of drying on the inositol phosphate concentrations in excreta.…”
Section: Introductionmentioning
confidence: 99%